Composite additive for preparing electrolytic copper foil, electrolyte and preparation method of electrolytic copper foil

By using a composite additive, it consists of two or more functional ionic liquids to promote the uniform deposition of copper grains, solve the problem of high roughness of the existing electrolytic copper foil, and realize the preparation of electrolytic copper foil with ultra -low outline. It is suitable for High -frequency high -speed PCB technology.

CN119372724APending Publication Date: 2025-01-28HENAN UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411553185.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The electrolytic copper foil prepared by the existing ionic liquid additives is still relatively high in roughness, which is difficult to meet the demand for low-profile copper foils by high-frequency and high-speed PCB technology.

Method used

The composite additives are composed of more than two or more functional ionic liquids. Through the synergistic role of different official groups, participate in the restore process of CU2+near the cathode, promote the uniform deposition of copper grains and reduce the surface roughness of the electrolytic copper foil.

Benefits of technology

The roughness of the prepared electrolytic copper foil surface is RZ ≤ 1.685 μm, and the minimum can be up to 0.531 μm, which significantly reduces the roughness of the surface of the copper foil and is suitable for the production of high -frequency high -speed PCB.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372724A_ABST
    Figure CN119372724A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrolytic copper foils, and particularly relates to a composite additive for preparing an electrolytic copper foil, an electrolyte and a preparation method of the electrolytic copper foil. The composite additive for preparing the electrolytic copper foil, disclosed by the invention, is selected from more than two of 1-hexyl-3-methylimidazole chlorine salt, 1-hydroxyethyl-3-methylimidazole chlorine salt, 1-butyl-3-methylimidazole tetrafluoroborate and 1-propyl-3-methylimidazole bromine salt. By compounding more than two kinds of functionalized ionic liquid, different functional groups in the functionalized ionic liquid can achieve a synergistic effect, so that the functionalized ionic liquid has a specific function and participates in the reduction process of Cu < 2 + > near a cathode, uniform deposition of copper grains is promoted, the ultra-low-profile electrolytic copper foil can be prepared, and the surface roughness of the copper foil is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrolytic copper foil, and in particular to a composite additive for preparing electrolytic copper foil, an electrolyte and a method for preparing the electrolytic copper foil. Background Art

[0002] In recent years, as global information technology has advanced towards digitalization and networking at an astonishing speed, the pursuit of ultra-large capacity information transmission, ultra-high speed and ultra-high density information processing capabilities has become the core goal of the development of information and communication equipment technology. At the same time, terminal electronic products continue to evolve towards ultra-thinness and ultra-lightness, further intensifying this technological pursuit. These technological innovations have brought unprecedented challenges to multiple fields such as system design, terminal product manufacturing processes, printed circuit boards (PCBs), copper clad laminates (CCLs), and copper foil manufacturing, thus triggering widespread attention and deep thinking in the industry on how to respond to these challenges.

[0003] Electrolytic copper foil, as an indispensable electronic and signal conduction medium in circuit boards, constitutes the core material of PCB manufacturing. With the rapid development of high-frequency and high-speed PCB technology, the demand for copper foil with low profile characteristics has increased dramatically. The root cause behind this surge in demand is that during the transmission of high-frequency and high-speed signals, the transmission line is susceptible to the effect of variable frequency fields, which causes a significant skin effect. The skin effect causes the current to be unevenly distributed inside the conductor and tends to gather on the surface of the conductor. The higher the signal frequency, the more significant this effect is, which in turn causes a significant increase in energy loss. In view of the significant influence of the "skin effect" in high-frequency circuit environments, in order to effectively reduce energy loss during signal transmission, low-profile copper foil is widely used because it can effectively suppress the adverse effects of the skin effect.

[0004] The Chinese patent application with application publication number CN116024618A, which was applied for and published on April 28, 2023, discloses an application of ionic liquid additives in electrolytic copper foil and a method for preparing high tensile strength and high elongation electrolytic copper foil. The electrolyte is prepared using a directed synthesized ionic liquid additive with an addition concentration of 10 mg / L~50 mg / L. The ionic liquids include 1-hexyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium chloride, 1-aminopropyl-3-methylimidazolium bromide, etc., so that they produce a synergistic promoting effect with sulfuric acid and copper sulfate in the electrolyte. The additive can simultaneously improve the tensile strength and elongation of the copper foil under the conditions of direct current electrodeposition process, and reduce the surface roughness and average grain size of the copper foil. The roughness Rz can be as small as 2.655μm.

[0005] However, the roughness of the electrolytic copper foil prepared by the ionic liquid additive used in the above method is still relatively high. Summary of the invention

[0006] The purpose of the present invention is to provide a composite additive for preparing electrolytic copper foil, so as to solve the problem of high roughness of the electrolytic copper foil prepared by using the existing ionic liquid additive.

[0007] The second object of the present invention is to provide an electrolyte for preparing electrolytic copper foil, so as to solve the problem that the electrolytic copper foil prepared by the existing electrolyte has high roughness.

[0008] The third object of the present invention is to provide a method for preparing an electrolytic copper foil, so as to solve the problem that the electrolytic copper foil prepared by the existing method for preparing an electrolytic copper foil has high roughness.

[0009] In order to solve the above technical problems, the technical solution of the composite additive for preparing electrolytic copper foil of the present invention is: A composite additive for preparing electrolytic copper foil, wherein the composite additive is selected from two or more of 1-hexyl-3-methylimidazolium chloride, 1-hydroxyethyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate and 1-propyl-3-methylimidazolium bromide.

[0010] The present invention improves the prior art and provides a composite additive for preparing electrolytic copper foil. By compounding two or more functionalized ionic liquids, different functional groups in the functionalized ionic liquids can work synergistically to make them have specific functions and participate in the electrolysis of Cu near the cathode. 2+ During the reduction process, the uniform deposition of copper grains is promoted, and ultra-low profile electrolytic copper foil can be prepared, reducing the surface roughness of the copper foil. The roughness Rz of the rough surface of the electrolytic copper foil prepared by the composite additive of the present invention is ≤1.685μm, and the lowest can be 0.531μm.

[0011] The ionic liquid composite additive process provided by the present invention has a wide application range, and the electrolyte has high stability after addition, which avoids the problems of repeated addition and impurity removal caused by the failure of the additive, improves the stability and simplicity of process control, and has practical significance for the production of copper foil for high-frequency and high-speed PCB.

[0012] In order to further reduce the roughness of the matte surface of the electrolytic copper foil, preferably, the composite additive is composed of two of 1-hexyl-3-methylimidazolium chloride, 1-hydroxyethyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate, and 1-propyl-3-methylimidazolium bromide, and the mass ratio of the two additives is (1-1.5): (1-1.5). The roughness Rz of the matte surface of the electrolytic copper foil prepared by using the composite additive is ≤1.685μm.

[0013] In order to further reduce the roughness of the matte surface of the electrolytic copper foil, preferably, the composite additive is composed of three of 1-hexyl-3-methylimidazolium chloride, 1-hydroxyethyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate, and 1-propyl-3-methylimidazolium bromide, and the mass ratio of the three additives is (1-1.5): (1-1.5): (1-1.5). The roughness Rz of the matte surface of the electrolytic copper foil prepared by using the composite additive is ≤0.935μm.

[0014] In order to further reduce the roughness of the matte surface of the electrolytic copper foil, preferably, the composite additive is composed of 1-hexyl-3-methylimidazolium chloride, 1-hydroxyethyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate and 1-propyl-3-methylimidazolium bromide in a mass ratio of (1-1.5): (1-1.5): (1-1.5): (1-1.5). The roughness Rz of the matte surface of the electrolytic copper foil prepared by using the composite additive is ≤0.531 μm.

[0015] The technical solution of the electrolyte for preparing electrolytic copper foil of the present invention is: An electrolyte for preparing electrolytic copper foil, the electrolyte consists of an electrolyte mother solution and a composite additive, the electrolyte mother solution includes CuSO4 and H2SO4, and the mass concentration of the composite additive in the electrolyte is 10-40 mg / L.

[0016] The electrolyte for preparing electrolytic copper foil provided by the present invention introduces a composite additive into the electrolytic mother solution, utilizes the synergistic effect of different functional groups of the composite additive, and then produces a synergistic promotion effect with sulfuric acid and copper sulfate in the electrolyte, so that ultra-low profile electrolytic copper foil can be prepared under electrodeposition process conditions; and the ionic liquid itself has the advantages of wide electrochemical window, high stability, good conductivity, non-volatile, etc., which can further improve the stability of the electrolytic copper foil electroplating solution.

[0017] In order to further improve the deposition quality of electrodeposition, preferably, the mass concentrations of CuSO4 and H2SO4 in the electrolyte are 50-90 g / L and 70-100 g / L, respectively.

[0018] The technical solution of the method for preparing the electrolytic copper foil of the present invention is: A method for preparing an electrolytic copper foil comprises the following steps: using the electrolyte to perform electrodeposition to obtain the electrolytic copper foil.

[0019] The method for preparing an electrolytic copper foil provided by the present invention can prepare an electrolytic copper foil with ultra-low profile by performing electrodeposition in an electrolyte added with a composite additive and utilizing the synergistic effect of different functional groups of the composite additive to promote uniform deposition of copper grains.

[0020] In order to further improve the deposition efficiency, preferably, the current density during electrodeposition is 10-40 A / dm 2 The temperature during electrodeposition is 30~50℃. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the SEM morphology of the rough surface of the electrolytic copper foil prepared without adding additives; Figure 2 This is a SEM morphology image of the matte surface of the electrolytic copper foil obtained by the composite additive in Example 3; Figure 3 This is a 3D profile image of the matte surface of the electrolytic copper foil obtained by the composite additive of Example 3; Figure 4 The cross-sectional curve diagram of the 3D profile of the matte surface of the electrolytic copper foil obtained by the composite additive in Example 3 along the X-axis direction; Figure 5 This is a cross-sectional curve diagram of the 3D profile of the matte surface of the electrolytic copper foil obtained with the composite additive in Example 3 along the Y-axis direction. DETAILED DESCRIPTION

[0022] The technical concept of the composite additive for preparing electrolytic copper foil of the present invention is as follows: The cations or anions of functionalized ionic liquids contain specific groups that play different roles in the preparation of electrolytic copper foil by electrodeposition, for example, Cl - and Br - Can participate in Cu near the cathode 2+ The reduction process of Cl - Can change Cu 2+ The conversion crystallization speed makes the copper foil grain structure and surface uniform and delicate.

[0023] The existing technology uses functionalized ionic liquids in Cu 2+ The role in the reduction process is to introduce two special groups into a single ionic liquid at the same time, so that the single ionic liquid has multiple regulatory functions, which can improve the tensile strength and elongation of the electrolytic copper foil, and at the same time reduce the surface roughness and average grain size of the copper foil.

[0024] The present invention combines two or more specific functionalized ionic liquids and utilizes the synergistic effect of specific functional groups in different functionalized ionic liquids to make them have specific functions. 2+ The uniform deposition of copper grains is promoted during the reduction process, thereby greatly reducing the roughness of the matte surface of the electrolytic copper foil and obtaining an electrolytic copper foil with ultra-low profile.

[0025] When the composite additive provided by the invention is used for electrodeposition, iridium-plated titanium is used as an anode and titanium is used as a cathode, and direct current electrodeposition is performed in an electrolyte to which the composite additive is added to obtain an electrolytic copper foil with an ultra-low profile.

[0026] In a specific embodiment, the cathode is mechanically polished before electrodeposition, and the mechanical polishing is to grind the cathode using sandpaper of 400-500, 800-900, 1200-1300, 2000-2100, and 2500-2600 meshes in sequence.

[0027] In a specific implementation, after the electrodeposition is completed, the surface of the obtained electrolytic copper foil is cleaned with deionized water and then dried with cold air.

[0028] In order to better understand the content of the present invention, the present invention will be further described below in conjunction with specific examples. The following examples are based on the technology of the present invention and provide detailed implementation methods and operating steps, but the protection scope of the present invention is not limited to the following examples.

[0029] 1. Specific embodiments of the composite additive for preparing electrolytic copper foil of the present invention The formula composition of the composite additive for preparing electrolytic copper foil of the present invention is shown in Table 1.

[0030] Table 1 Formula composition of composite additives The composite additive for preparing electrolytic copper foil in Example 1 is composed of 10 mg of 1-propyl-3-methylimidazolium bromide ([C3MIM]Br) and 10 mg of 1-hydroxyethyl-3-methylimidazolium chloride ([EOHMIM]Cl).

[0031] The composite additive for preparing electrolytic copper foil of Example 2 consists of 10 mg 1-propyl-3-methylimidazolium bromide ([C3MIM]Br), 10 mg 1-hydroxyethyl-3-methylimidazolium chloride ([EOHMIM]Cl) and 10 mg 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM]BF4).

[0032] The composite additive for preparing electrolytic copper foil of Example 3 consists of 10 mg 1-propyl-3-methylimidazolium bromide ([C3MIM]Br), 10 mg 1-hydroxyethyl-3-methylimidazolium chloride ([EOHMIM]Cl), 10 mg 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM]BF4) and 10 mg 1-hexyl-3-methylimidazolium chloride ([HMIM]Cl).

[0033] 2. Specific embodiments of the electrolyte for preparing electrolytic copper foil of the present invention The formulation composition of the electrolyte for preparing electrolytic copper foil of the present invention is shown in Table 2. The electrolyte is obtained by adding the composite additives of Examples 1-3 to the electrolytic mother solution respectively; wherein the electrolytic mother solution is prepared from analytical pure copper sulfate, sulfuric acid and water, and the copper concentration in the electrolyte is the mass of commercially available analytical pure copper sulfate added to a certain volume of water, and similarly, the sulfuric acid concentration is the mass of commercially available concentrated sulfuric acid (mass fraction 98%) added to water.

[0034] Table 2 Electrolyte formulation composition The electrolyte for preparing electrolytic copper foil in Example 4 is composed of an electrolytic mother solution and the composite additive in Example 1. 2+ , H2SO4, and composite additives were 90 g / L, 100 g / L, and 20 mg / L, respectively. The composite additive consisted of [C3MIM]Br and [EOHMIM]Cl. The mass concentrations of [C3MIM]Br and [EOHMIM]Cl in the electrolyte were 10 mg / L and 10 mg / L, respectively.

[0035] The electrolyte for preparing electrolytic copper foil in Example 5 is composed of an electrolytic mother solution and the composite additive in Example 2. 2+ , H2SO4, and composite additives were 90 g / L, 100 g / L, and 30 mg / L, respectively. The composite additive consisted of [C3MIM]Br, [EOHMIM]Cl, and [BMIM]BF4. The mass concentrations of [C3MIM]Br, [EOHMIM]Cl, and [BMIM]BF4 in the electrolyte were 10 mg / L, 10 mg / L, and 10 mg / L, respectively.

[0036] The electrolyte for preparing electrolytic copper foil in Example 6 is composed of an electrolytic mother solution and the composite additive in Example 3. 2+ , H2SO4, and composite additives were 90 g / L, 100 g / L, and 40 mg / L, respectively. The composite additives consisted of [C3MIM]Br, [EOHMIM]Cl, [BMIM]BF4, and [HMIM]Cl. The mass concentrations of [C3MIM]Br, [EOHMIM]Cl, [BMIM]BF4, and [HMIM]Cl in the electrolyte were 10 mg / L, 10 mg / L, 10 mg / L, and 10 mg / L, respectively.

[0037] 3. Specific embodiments of the method for preparing the electrolytic copper foil of the present invention Example 7 The preparation method of the electrolytic copper foil of this embodiment is as follows: Step A: using iridium-plated titanium as an anode and titanium as a cathode, mechanically polishing the cathode titanium, wherein the cathode titanium is polished using 400, 800, 1200, 2000, and 2500 mesh water-abrasive sandpaper in sequence, and the cathode titanium surface after mechanical polishing is deionized and rinsed; Step B: preparing the electrolytes of Examples 4-6 and placing them in electrolytic cells respectively; Step C: Adjust the temperature of the electroplating solution in step B, and after the temperature reaches 50°C, perform direct current electrodeposition at a current density of 40 A / dm 2 ; Step D: The electrolytic copper foil obtained after the electrodeposition is rinsed with deionized water, and then dried with cold air.

[0038] IV. Experimental Examples Experimental Example 1 In this experimental example, the rough surface morphology of the prepared electrolytic copper foil was characterized. Figure 1 This is the SEM morphology of the rough surface of the electrolytic copper foil prepared without adding additives; Figure 2-3 They are respectively the SEM morphology image and the 3D contour morphology image of the rough surface of the electrolytic copper foil obtained by the composite additive in Example 3; Figure 4-5 They are cross-sectional curve diagrams of the 3D profile of the matte surface of the electrolytic copper foil obtained with the composite additive in Example 3 along the X-axis and Y-axis directions.

[0039] from Figure 1-5 It can be seen that after adding the composite additive provided by the present invention, the rough surface profile of the electrolytic copper foil is greatly improved, the surface becomes very smooth, and the roughness is greatly reduced.

[0040] Experimental Example 2 This experimental example illustrates the screening process of the formula composition of the composite additive provided by the present invention.

[0041] Different ionic liquids were selected to form composite additives, and the roughness Rz of different formulations was tested to screen the formulation composition of the composite additive. The formulation composition during screening is shown in Table 3.

[0042] Table 3 Formulation composition during screening Composition (mg) 1# 2# 3# 4# 5# 6# 7# 8# [HMIM]Cl 10 10 [EOHMIM]Cl 10 20 10 10 10 <![CDATA[[BMIM]BF4]]> 10 10 10 <![CDATA[[C3MIM]Br]]> 10 10 10 10 The composite additive of the above formula was used, and the electrolyte was prepared according to Example 4, and then the electrolytic copper foil was prepared according to the preparation method of the electrolytic copper foil of Example 7, and the roughness Rz of the rough surface of the electrolytic copper foil was tested by JD-520 roughness meter. The specific test method is as follows: the copper foil is placed on a flat operating table, and the copper foil is tested three times in the horizontal and vertical directions using the roughness meter, and the average value of the six experimental results is taken as the test result of the roughness Rz. The test results are shown in Table 4.

[0043] Table 4 Test results of roughness of electrolytic copper foil Roughness Rz (µm) No additives added 3.771 1# 2.865 2# 2.763 3# 2.935 4# 2.762 5# 2.416 6# 1.685 7# 0.935 8# 0.531 As can be seen from Table 4, compared with no additives, the roughness of the rough surface of the electrolytic copper foil prepared by adding additives (1#~8#) is significantly reduced; and compared with a single ionic liquid as an additive (1#~5#), the composite additives formed by multiple ionic liquids (6#~8#) show a lower roughness of the rough surface; in particular, compared with 5# (single-component additive [EOHMIM]Cl), 6# formula (two-component additives [EOHMIM]Cl and [C3MIM]Br) shows a lower roughness, indicating the synergistic effect of multi-component additives in improving the roughness of the rough surface of the electrolytic copper foil; the component formula of 6#~8# composite additives is Examples 1-3 of the present invention. In addition, as the number of ionic liquid composites increases, the roughness of the rough surface is lower, and the lowest can be as low as 0.531µm.

[0044] The stability of the electrolyte formed by the above-mentioned composite additives was tested to prove that the ionic liquid composite additive electrolyte of the present invention has super high stability. The specific tests are as follows: 1) The high stability of the plating solution was evaluated by continuous preparation of copper foil: copper foil was continuously prepared 50 times in the electrolyte formed by the 8# composite additive formula, and no significant change was found in the copper foil performance; while the copper foil prepared with gelatin as an additive showed a significant decline in copper foil performance after 20 consecutive preparations; 2) After long-term continuous preparation of copper foil, UV-vis analysis was performed on the plating solution, and no change occurred in the ionic liquid composition, indicating that the long-term preparation did not decompose the ionic liquid, proving the high stability of the plating solution of the present invention.

[0045] The present invention can have other forms of embodiments according to the above preparation method, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made to the above embodiments by any technician familiar with the profession according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A composite additive for preparing electrolytic copper foil, characterized in that: The composite additive is selected from two or more of 1-hexyl-3-methylimidazolium chloride, 1-hydroxyethyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate, and 1-propyl-3-methylimidazolium bromide.

2. The composite additive for preparing electrolytic copper foil according to claim 1, characterized in that: The composite additive is composed of two of 1-hexyl-3-methylimidazolium chloride, 1-hydroxyethyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate, and 1-propyl-3-methylimidazolium bromide, and the mass ratio of the two additives is (1-1.5): (1-1.5).

3. The composite additive for preparing electrolytic copper foil according to claim 1, characterized in that: The composite additive is composed of three of 1-hexyl-3-methylimidazolium chloride, 1-hydroxyethyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate, and 1-propyl-3-methylimidazolium bromide, and the mass ratio of the three additives is (1-1.5): (1-1.5): (1-1.5).

4. The composite additive for preparing electrolytic copper foil according to claim 1, characterized in that: The composite additive consists of 1-hexyl-3-methylimidazolium chloride, 1-hydroxyethyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate and 1-propyl-3-methylimidazolium bromide in a mass ratio of (1-1.5):(1-1.5):(1-1.5):(1-1.5).

5. An electrolyte for preparing electrolytic copper foil, characterized in that: The electrolyte consists of an electrolyte mother solution and the composite additive according to any one of claims 1 to 4, wherein the electrolyte mother solution includes CuSO4 and H2SO4, and the mass concentration of the composite additive in the electrolyte is 10-40 mg / L.

6. The electrolyte for preparing electrolytic copper foil according to claim 5, characterized in that: The mass concentrations of CuSO4 and H2SO4 in the electrolyte are 50~90 g / L and 70~100 g / L, respectively.

7. A method for preparing an electrolytic copper foil, characterized in that: The following steps are involved: The electrolytic copper foil is obtained by electroplating using the electrolyte described in claim 5 or 6.

8. The method for preparing an electrolytic copper foil according to claim 7, characterized in that: The current density during electrodeposition is 10~40 A / dm 2 The temperature during electrodeposition is 30~50℃.

Citation Information

Patent Citations

  • Application of ionic liquid additive in electrolytic copper foil and preparation method of high-tensile high-elongation electrolytic copper foil

    CN116024618A